Rasionalitas Amil Zakat Komunitas: Studi di Kota Ambon Maluku - Subair, Subair (Tasamuh: Jurnal Studi Islam, 2019)
The knowledge construction of community tithe is result from knowledge and power rezim overcome through objectivity, internalization and externalisation which go on as dialectic and simultaneous. The prosess involves synthesis of religion and local knowledge, and it is cuonstructed through tithe (zakat) knowledge to be basis of culture which based on the religion. Rationality Friction (rationality shift) is taken place (happened) in tradition be tithe and carried uot, organized. Later, Is found or met with rationality modification follow the tithe fenomenon which is built by tithe discourse. Rationality which is built from the grass knowledge system fuses, and even it always is defeated by building of knowledge rationality of community tithe